On line extraction and separation of bendiocarb, methomyl, methylparathion, and pentachlorophenol pesticides from raw milk - Menezes, Manoel Lima de [UNESP]; Felix, G. (Marcel Dekker Inc, 1998)
A high performance liquid chromatography (HPLC) method for extraction and determination of pesticides from raw milk was developed. The method involves direct injection of raw milk samples on a bovine serum albumin-dimethyl-octyl-silica gel (BSA-Si-Cs) column. The mobile phase 0.05 mol.L-1 phosphate buffer pH6.0 in acetonitrile (70:30 v/v) was employed for extraction and separation of bendiocarb, methylparathion, pentachlorophenol, and methomyl pesticides. The method shows good results of recovery in the pesticides studied, higher than 99.6%.